PERAN OJK MELALUI PERATURAN NOMOR 71/POJK.05/2016 TENTANG KESEHATAN KEUANGAN PERUSAHAAN ASURANSI DAN PERUSAHAAN REASURANSI TERHADAP PERUSAHAAN ASURANSI YANG MEMILIKI TINGKAT KESEHATAN KEUANGAN RENDAH - Suhandi Suhandi; Christine S. T. Kansil (Fakultas Hukum Universitas Tarumanagara, 2022)
insurance agreement in nowaday isn't only as a protection of healthiness and asset, nowadaysinsurance is also used as an investment . there are so many insurance company nowadays that couldbe a choice for society. because there are so many dif erent insurance company, it makes a competitionbetween them, as a result they are trying to make a new product that could make an interest frompeople. however, the product is not always made well and their management of risk is often poor so itneed to supervision by a institution. As an example, Jiwasraya that made a product that called JSSaving Plan that made high loss for the state. in Indonesia, OJK is a authority that made especiallywith a function of regulating, evaluating, and investigation for every institution that works with afinancial scope. as a duty of OJK, they made a regulation that made especially for regulating thefinancial health of the insurance company that can be found on POJK Nomor 71 Tahun 2016 and someof SEOJK that made as a guidelines for the company to managing their financial health and also thefinancial statement.in the practice, there are a loop hole from the regulation that can be an obstaclefor OJK to diagnose the poor financial level of the company. while the financial health of the companyis an important thing to avoid the loss for the people.